LA FORMA DE CUMPLIMIENTO DE LA PENA DE LAS PERSONAS PRIVADAS DE LA LIBERTAD EN CENTROS ESPECIALES DE REHABILITACIÓN SOCIAL PARA GARANTIZAR EL DERECHO A LA SALUD - Maldonado Pineda., Thalia Paola (2019)
This thesis constitutes the final report of the investigation process conducted in a motivated manner based on the provisions of the Constitution of the Republic of Ecuador. And in view of the fact that the Comprehensive Criminal Organic Code does not consider people who suffer from rare or orphan diseases, catastrophic, in the separation of persons for the execution of sentences; communicable and non-communicable diseases that require continuous care, I have identified my problem because the way in which they have to serve their custodial sentence without transferring them to a public or private hospital, which is the form now Art.669 of the Comprehensive Criminal Organic Code. Therefore, the right to health of these people deprived of liberty in a comprehensive manner, or other persons who are not deprived of their liberty, and then they must share even hospital beds and that entails putting their own integrity at risk, in this way, it is necessary to guarantee integral health in centers of deprivation of liberty specific to people suffering from rare or orphan diseases, catastrophic; communicable and non-communicable diseases that require continuous care. Contains conceptual references and doctrinal elements that allow the understanding of the legal issues and as a result of this inquiry process I allow myself to formulate as a proposal a Public Policy to guarantee the right to health of the People Deprived of Liberty in the Social Rehabilitation Centers of Ecuador , it is so that after the investigation I show that it is necessary to establish as a public policy the creation of a specialized medical pavilion inside the different Social Rehabilitation Centers of the country, for people deprived of freedom who suffer rare or orphan diseases, catastrophic, transmissible and non-communicable diseases that require continuous care; where the right to health of people deprived of their liberty is guaranteed.